Electrophysiological assessment of retinal ganglion cell function - Porciatti, Vittorio (Exp Eye Res, 2015)
The function of retinal ganglion cells (RGCs) can be non-invasively assessed in experimental and genetic models of glaucoma by means of variants of the ERG technique that emphasize the activity of inner retina neurons. The best understood technique is the Pattern Electroretinogram (PERG) in response to contrast-reversing gratings or checkerboards, which selectively depends on the presence of functional RGCs. In glaucoma models, the PERG can be altered before histological loss of RGCs; PERG alterations may be either reversed with moderate IOP lowering or exacerbated with moderate IOP elevation. Under particular luminance-stimulus conditions, the Flash-ERG displays components that may reflect electrical activity originating in the proximal retina and be altered in some experimental glaucoma models (positive Scotopic Threshold response, pSTR; negative Scotopic Threshold Response, nSTR; Photopic Negative Response, PhNR; Oscillatory Potentials, OPs; multifocal ERG, mfERG). It is not yet known which of these components is most sensitive to glaucomatous damage. Electrophysiological assessment of RGC function appears to be a necessary outcome measure in experimental glaucoma models, which complements structural assessment and may even predict it. Neuroprotective strategies could be tested based on enhancement of baseline electrophysiological function that results in improved RGC survival. The use of electrophysiology in glaucoma models may be facilitated by specifically designed instruments that allow high throughput, robust assessment of electrophysiological function.